2001
DOI: 10.1002/pen.10726
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of reactive and non‐reactive blends of ethylene‐methyl acrylate copolymers with styrene‐maleic anhydride copolymer

Abstract: The effects of compatibilizing reactions on the viscoelastic properties and morphology of ethylene-methyl acrylate copolymers were studied. Potentially reactive blends of styrene-maleic anhydride copolymer (SMAH) and a terpolymer of ethylene/methyl acrylate/glycidyl methacrylate (E-MA-GMA) were compared with a nonreactive blend of SMAH and an ethylene/methyl acrylate (E-MA) copolymer with similar rheological properties. Melt mixing was carried out in a batch mixer and in a co-rotating twin screw extruder. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It has been shown that several thermoplastics after reactive modification by chain extension exhibit a more enhanced shear‐thinning behavior in the lower shear‐rate region, which is attributed to a long‐time‐relaxation mechanism, such as entanglement couplings between the high MW fraction and those associated with long‐chain branches. However, broadening the relaxation time distribution is also responsible for the weak level of shear thinning in the higher shear‐rate region 7, 28, 29. The modified PET produced in this work consisted of gel particles dispersed in a polymeric melt, as demonstrated by the data in Figure 6.…”
Section: Resultsmentioning
confidence: 86%
“…It has been shown that several thermoplastics after reactive modification by chain extension exhibit a more enhanced shear‐thinning behavior in the lower shear‐rate region, which is attributed to a long‐time‐relaxation mechanism, such as entanglement couplings between the high MW fraction and those associated with long‐chain branches. However, broadening the relaxation time distribution is also responsible for the weak level of shear thinning in the higher shear‐rate region 7, 28, 29. The modified PET produced in this work consisted of gel particles dispersed in a polymeric melt, as demonstrated by the data in Figure 6.…”
Section: Resultsmentioning
confidence: 86%
“…The majority of previous rheological studies on reactively compatibilized polymer blends mainly focused on their linear viscoelastic behavior. 11,12 Reactive compatibilization significantly increases the complex modulus of blends of polyamide 6 (PA 6) and styrenic polymers in the low frequency range. 13 Quantitative analysis of the linear viscoelastic data using the extended model of Palierne 14,15 revealed that the physical principles which were established for physically compatibilized blends with preformed compatibilizing agents 16,17 are also valid for in situ compatibilized blends.…”
Section: Introductionmentioning
confidence: 99%
“…The melt behavior is considered to be more elastic if it is located further right [35] . The data of the chain-extended copolyester with a higher PPDI content was further on the right side and approached the 45 ° line at all frequencies, whereas the unreacted copolyester could not approach the 45 ° line, even at high frequencies.…”
Section: Rheological Properties Of the Chain-extended Copolyestermentioning
confidence: 99%